THE ROLE OF DIVIDEND POLICY IN INCREASING THE LEVEL OF BANK CAPITALIZATION - Rufat Bakhtiyorovich Kurbanov (American Journals, 2023)
The article examines foreign and domestic literature to show the role of dividend policy of commercial banks in increasing the level of capitalization of banks and examines the advantages of a regular dividend policy. In particular, when studying the scientific views of researchers, a number of shortcomings and issues in the dividend policy of commercial banks were identified. Also, commercial banks are examined as active participants in the stock market, as well as financial data on dividends payout was investigated. Based on the research conducted, conclusions and practical recommendations were established.
Keywords: Commercial bank, stock, dividend, dividend policy, capital, investor.